Fifty Shades of Black: Challenging the Monolithic Treatment of “Black or African American” Candidates on Law School Admissions Applications - Eteena A. Tadjiogueu (Washington University Journal of Law & Policy, 2014)
Law school applicants who identify as “Black or African American” are afforded little opportunity to identify more specifically their ancestral or cultural heritage, if it is known, on law school admissions applications. Seemingly, some law schools have not found it necessary to allow certain groups, such as Haitian Americans, Black Britons, second-generation Nigerians, Black American nationals, and others, to designate their ethnic identity in the same manner that Chinese Americans, second-generation Koreans, naturalized Vietnamese citizens, and other Asians are able to within the “Asian” racial category on some law school admissions applications. Despite identifiable, important, and growing differences within the “Black or African American” racial category, individuals who identify with this group are treated as members of a monolithic unit. This Note argues that this categorization, like the “one-drop rule,” reinforces a social construction developed to demonize and demoralize a sizeable segment of the American population, and that the singular treatment of Black law school applicants is a potential threat to diversity initiative programs. This Note will discuss proposals to reform the “Black or African American” category on law school admissions applications, and will argue that proposals to include greater and more precise options for identification within the “Black or African American” category should be adopted. This inclusion will enable applicants to self-identify in a manner similar to other racial groups, thus enhancing the accuracy of identifications and decreasing the demoralizing effect monolithic treatment has on Black applicants. Reform will also reduce incidences of misrepresentation.
Keywords: law school application; one-drop rule; racial diversity; Fisher v. University of Texas; self-identify; diversity initiative; Black or African-American; Equal Protection Clause; Bakke; diversity factor; racial discrimination; diversity information; black applicant; immigrant black; under-inclusive; reporting requirement